Gestational Diabetes Mellitus and Energy-Dense Diet: What Is the Role of the Insulin/IGF Axis? - Martín-Estal, Irene; Castorena-Torres, Fabiola (Frontiers in Endocrinology, 2022)
Gestational diabetes mellitus (GDM), is one of the most important pregnancy complications affecting approximately 15 % of pregnant women. It is related to several gestational adverse outcomes in the fetus, e.g., macrosomia, shoulder dystocia, stillbirth, neonatal hypoglycemia, and respiratory distress. Women with GDM have a high risk of developing type 2 diabetes in the future. The pathogenesis of GDM is not completely understood; nevertheless, two factors could contribute to its development: β-cell dysfunction and failure in insulin secretion in response to insulin resistance induced by gestation. Both processes, together with the physiological activities of the insulin-like growth factors (IGFs), play a crucial role in glucose transport to the fetus and hence, fetal growth and development. IGFs (both IGF-1 and IGF-2) and their binding proteins (IGFBPs) regulate glucose metabolism and insulin sensitivity. Maternal nutritional status determines the health of the newborn, as it has substantial effects on fetal growth and development. Maternal obesity and an energy-dense diet can cause an increase in insulin and IGF-1 serum levels, producing metabolic disorders, such as insulin resistance, GDM, and high birth weight (> 4,000 g) due to a higher level of body fat. In this way, in GDM pregnancies there is an increase in IGF-1 and IGF-2 serum levels, and a decrease in IGFBP-1 and 4 serum levels, suggesting the crucial role of the insulin/IGF system in this gestational outcome. Here, the present review tries to elucidate the role that energy-dense diets and the insulin/IGF-1 signaling pathway perform in GDM pregnancies.